A comprehensive small angle X-ray scattering analysis on morphological structure of semicrystalline linear polymer in bulk state. (14th March 2022) - Kim, Changsub; Jarumaneeroj, Chatchai; Rungswang, Wonchalerm; Jin, Kyeong Sik; Ree, Moonhor
Abstract: In this study, we attempted to conduct a comprehensive small angle X-ray scattering (SAXS) analysis on the microstructure of a representative semicrystalline linear thermoplastic, polyethylene in bulk state using synchrotron radiation source. The scattering measurements and data analyses were performed by considering the range of scattering angle and its impacts, the proper correction of background scattering and its impacts, the merits and limitations of qualitative data analysis schemes, and the feasibilities of quantitative data analysis schemes in order to gain insights into the microstructure in a very complex nature associated with the structural dimension and orientation distributions. The SAXS scattering analysis is widely adopted with a limited angle range because of various reasons; but it was confirmed to cause overestimation and/or underestimation in the structural parameters because of the lack of scattering data in the Porod regime. Thereby, SAXS measurements should be essential with the range of scattering angle that fully covers the Porod regime as well as a part of the background scattering solely and then include background scattering correction. The paracrystal model scheme, as one of the quantitative methods, was found to be able to fit the experimental scattering profile in a more appropriate manner. But, the scattering profile part in the large angle region could yet be fitted; furthermore, the crystalline and amorphous layer thicknesses were overestimated due to ignoring the presence of transition layer. All other schemes could unsatisfactorily fit the experimental scattering data and, thereby, estimate only structural parameters. Even for such estimations, the quantitative model schemes were confirmed to provide structural parameters in less errors, compared to the qualitative analysis methods. Graphical abstract: Image 1 Highlights: Comprehensive SAXS analysis is performed on microstructure of bulk PE. q-Range covering a full Porod regime is essential in SAXS measurement. Background scattering subtraction is necessary before SAXS data analysis. Quantitative SAXS data analyses produce structural parameters in less errors. Qualitative SAXS data analyses cause more errors in structural parameters.